FACTORS AFFECTING THE INTEREST OF ACCOUNTING STUDENTS TO TAKE PROFESSIONAL ACCOUNTANT CERTIFICATION - Natalia Lily Babulu; Paulina Rosna Dewi Redjo (Jurnal Ekonomi, 2022)
The accounting profession as one of the professions with good prospects of course also cannot be separated from certification requirements. An accountant with a professional accountant certification is expected to be able to manage reports and make business decisions. This certification is a form of acknowledgment of a person's competence, knowledge and skills. Certified accountants will be considered more competent than accountants who do not have certification. Adequate information about accounting certification will provide a comprehensive understanding so that it has an impact on the strong desire of students to take professional accountant certification. One form of the selling point of accounting graduates who demonstrate the competency of graduates' skills is the possession of a professional accountant certificate. The purpose of the study was to determine student interest in taking professional accountant certification. The data collection method used is using questionnaires distributed to all 7th semester accounting students. Data analysis of this study uses SmartPLS 4. The results of this study indicate that the level of understanding affects the demand for students to follow professional accountant certification, economic motivation does not affect student interest in following certification. professional accountants and labor market considerations affect student interest in taking professional accountant certification